PKM ALAT PENARIK RUMPUT LAUT DAN PEMBERDAYAAN MELALUI DIVERSIFKASI PRODUK OLAHAN RUMPUT LAUT PADA KELOMPOK KARYA BERSAMA MAMPIE POLEWALI MANDAR - Arifin, Asia; Ilham, Ilham; Ali, Baso; Rosman N, Andi (Jurnal Abdi Insani, 2024)
The people of Galeso Village in Polewali Mandar Regency depend on seaweed farming as their main source of income. However, there are several obstacles such as long seaweed removal time and limited knowledge about processing seaweed into high-value products. The purpose of this Community Partnership Service (PKM) activity is to increase partners' knowledge and skills in using mechanized seaweed pulling technology and processing seaweed into high-value products. The methods used included situation analysis, counseling, training and mentoring, and evaluation. Activities were carried out through lectures, questions and answers, and hands-on practice by participants. Pretest and posttest were used to measure the improvement of participants' knowledge and skills. The results showed a significant increase in participants' knowledge and skills in using technology and processing seaweed. This was reflected in the 79.80% increase in participants' posttest scores compared to the pretest. Participants also showed high satisfaction with the implementation of the training. The PKM activities succeeded in achieving the objectives by increasing the ability and knowledge of partners, which is expected to increase the sustainability of seaweed cultivation businesses in Galeso Village and its surroundings.